Intersectionalities and im/mobilities in family and marriage: a comparative study of Germany and India - Mayurakshi Chaudhuri; Saurav Karmakar; Sakshi Shukla (Humanities & Social Sciences Communications, 2024)
Abstract This article investigates comparative intersections of gender and family sociology internationally, with a specific focus on urban Germany and urban India. In particular, this research examines a central dynamic that informs family and marriage relations globally, and for this research context, in Germany and India: What are the nuanced ways of conceptualizing changing gender roles in marriage and in family in Germany and India? Bringing together a robust understanding of the theoretical frameworks of Intersectionality and of Mobility as large bodies of scholarship that examine geographic and symbolic power geometries, we adopt the lens of Intersectional Im/Mobilities to explore changing gender roles in family and marriage in Germany and India. We particularly focus on an intersectionality-based analysis of two primary themes that arise out of our primary and secondary data: (1) Women’s employment and impact on family life/work–life balance; and (2) Changing gender roles in marriage (through the lens of the division of household labor and aspects of agency and decision making), questions which influence and inflect complex intersectional realities.